1999
DOI: 10.1042/bj3420697
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of the Src-homology-2-domain-containing inositol 5-phosphatase SHIP-2 in both non-haemopoietic and haemopoietic cells and possible involvement of SHIP-2 in negative signalling of B-cells

Abstract: The termination of activation signals is a critical step in the control of the immune response; perturbation of inhibitory feedback pathways results in profound immune defects culminating in autoimmunity and overwhelming inflammation. FcγRIIB receptor is a well described inhibitory receptor. The ligation of B-cell receptor (BCR) and FcγRIIB leads to the inhibition of B-cell activation. Numerous studies have demonstrated that the SH2-domain-containing inositol 5-phosphatase SHIP (referred hereto as SHIP-1) is e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 78 publications
(41 citation statements)
references
References 35 publications
2
39
0
Order By: Relevance
“…This difference in severity is most likely because SHIP2 is expressed to some degree in hemopoietic cells (Muraille et al 1999), while SHIP is not expressed in nonhemopoietic tissues ) and therefore cannot compensate for the loss of SHIP2. In addition, as shown in Fig.…”
Section: The Phenotype Of Ship-deficient Micementioning
confidence: 97%
See 1 more Smart Citation
“…This difference in severity is most likely because SHIP2 is expressed to some degree in hemopoietic cells (Muraille et al 1999), while SHIP is not expressed in nonhemopoietic tissues ) and therefore cannot compensate for the loss of SHIP2. In addition, as shown in Fig.…”
Section: The Phenotype Of Ship-deficient Micementioning
confidence: 97%
“…This transiently generated PI-3,4,5-P 3 attracts pleckstrin homology (PH) domaincontaining proteins to the plasma membrane to mediate its effects (Rameh and Cantley 1999;Huber et al 1999). To ensure that the activation of this pathway is appropriately suppressed/terminated, the ubiquitously expressed tumor suppressor PTEN hydrolyzes PI-3,4,5-P 3 back to PI-4,5-P 2 (Maehama and Dixon 1998;Stambolic et al 1998) while the 145-kDa hemopoietic-restricted SH2-containing inositol 5 0 -phosphatase, SHIP (also known as SHIP1; Huber et al 1999), the 104-kDa stem cell-restricted SHIP (sSHIP; Tu et al 2001) and the more widely expressed 150-kDa SHIP2 (Pesesse et al 1997;Wisniewski et al 1999;Pesesse et al 1998;Muraille et al 1999) break it down to PI-3,4-P 2 (Fig. 1A).…”
Section: Introductionmentioning
confidence: 98%
“…Interestingly, no significant difference in the phosphatase activity of SHIP was found between unstimulated cells and cytokine-stimulated cells, suggesting the importance of localization of SHIP to the membrane for its function [97]. SHIP2 is expressed in many cells, including in T cells [116][117][118]. Cloning of the cDNA for SHIP2 revealed high homology to SHIP especially in the SH2 domain.…”
Section: Shipmentioning
confidence: 99%
“…Interestingly, SHIP2-deficient mice die perinatally from insulin-hypersensitivity-induced hypoglycaemia [23]. This is a far more severe phenotype than that observed with SHIP −/− mice [24], most probably because SHIP2 is expressed, to some degree, in haemopoietic cells [25], whereas SHIP is not expressed in non-haemopoietic tissues [26] and therefore cannot compensate for the loss of SHIP2. Related to this, the proline-rich C-terminus of SHIP, which we [27] and Aman et al [28] have shown recently to be essential for SHIP function in bone-marrow-derived mast cells (BMMCs) and B-cells respectively, is very different from that of SHIP2 [29] and may allow for differential regulation.…”
Section: Introductionmentioning
confidence: 99%
“…This phospholipid is present at low levels in resting cells, but is rapidly synthesized from PtdIns(4,5)P 2 (PI-4,5-P 2 ) by PI3K, in response to a diverse array of extracellular stimuli, and attracts pleckstrin homology (PH)-containing proteins to the plasma membrane to mediate its effects [2,3]. To ensure that the activation of this pathway is appropriately suppressed or terminated, the tumour suppressor PTEN (phosphatase and tensin homologue deleted on chromosome 10) hydrolyses this phospholipid back to PI-4,5-P 2 [4,5], whereas the haemopoietic-specific Src homology 2-containing inositol 5 -phosphatases (SHIPs), SHIP1 [3] and the more ubiquitous SHIP2 [6][7][8][9] break it down to PtdIns(3,4)P 2 (PI-3,4-P 2 , which may also act as a second messenger in some cells [2,10,11]). The fact that almost 50% of human cancers contain bi-allelic inactivating mutations of PTEN [12] highlights the importance of tightly regulating the PI3K pathway.…”
Section: Introductionmentioning
confidence: 99%